EFFECT OF OXIDIZING AGENTS IN EXTRACTING GOLD FROM ANODE SLIME - Isyatun Rodliyah; Nuryadi Saleh; Ngurah Ardha; Zaki Mubarok (Puslitbang tekMIRA, 2013)
Anode slime is a byproduct collected from electro refining copper process. The valuable metals present in the slime are Au, Ag, Pt, Pd and Pb. Yet, the slime has not been processed in Indonesia but sent to another country. Extracting the gold from anode slime had been attempted in the laboratory by applying wet chlorination method. Sodium hypochlorite (NaOCl) and hydrogen peroxide (H2O2) served as the oxidizing agents. Effects of various parameters such as solvent concentration, leaching time and temperature on the percent extraction of gold were studied. The optimum recovery of gold with NaOCl is 98.86 % Au at leaching temperature of 40°C, solvent concentration 5 M, NaOCl 5 mL and 20% solid after 120 minutes leaching time. Silver loss under this condition is 2–3%. Leaching the gold by H2O2 provided the highest gold extraction of 99.99% Au at 7M HCl concentration, temperature 60°C, H2O2 0.5 M, leaching time 180 minutes, and 20% solid. The silver loss under this condition is only 0.6%.